HARMONI SENSE OF URGENCY PEREMPUAN PERISIR, ADAPTASI CLIMATE CHANGE DAN PENGUATAN EKONOMI KELUARGA - Tri Cahya, Bayu; Marpaung, Muslim; Ihsan; Candra Dinar Mulyaningtyas, Putri (Proceedings of Annual Conference on Community Engagement, 2023)
Women's nature is generally obliged to carry out domestic roles. But in reality, not a few women perform public functions to meet the family's needs. This study uses qualitative methods (Ethnography) by collecting data from interviews, observations, and documentation. The purpose of this study is to reveal the convergence of Coastal Women's Sense of Urgency, Climate Change Adaptation, and Family Economic Strengthening in the coastal area of Pati district. Coastal women who are the research subjects are the wives of fishermen in the area. Based on the results of the study it was found that the background of the role of salt farmers' wives is economic factors and the availability of opportunities in carrying out public roles. Women's efforts to support the family economy, namely the majority of women work as salt farmers, traders, and laborers in salt packing factories. The contribution of the dual role of women in carrying out public functions is to fulfill the economic needs of the family.